Unexpected Colonial Returns: Self-Selection and Economic Integration of Migrants over Multiple Generations - Anne C. Gielen; Dinand Webbink (Institute of Labor Economics (IZA), 2023)
A ban on migration from Suriname, a former Dutch colony, to the Netherlands induced a mass migration and changed the selection of migrants. We exploit this historical episode to study the relationship between the self-selection of migrants and their long-term economic integration over three generations. 'Beat-the-ban' migrants, those arriving just before the ban, are negatively selected compared to economic migrants arriving earlier. This difference in selection is reflected in the outcomes of the first generation. However, the inequality in outcomes between differently selected migrants is not persistent. The offspring of negatively selected migrants has a faster catch-up to natives which can be explained by inequities in the country of origin.
Keywords: J24; J6; 330; mass migration; economic integration; intergenerational mobility; migrant selection